2021
DOI: 10.1002/ajmg.a.62365
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genotypic spectrum of PYCR2 and a common ancestry in Thai patients with hypomyelinating leukodystrophy 10

Abstract: PYCR2 pathogenic variants lead to an autosomal recessive hypomyelinating leukodystrophy 10 (HLD10), characterized by global developmental delay, microcephaly, facial dysmorphism, movement disorder, and hypomyelination. This study identified the first two unrelated Thai patients with HLD10. Patient 1 harbored the novel compound heterozygous variants, c.257T>G (p.Val86Gly) and c.400G>A (p.Val134Met), whereas patient 2 possessed the homozygous variant, c.400G>A (p.Val134Met), in PYCR2. Haplotype analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Lossof-function mutations in PYCR2 gene result in HLD10, which is identified by hypomyelination, global growth delay, microcephaly, facial dysmorphism, axial hypotonia, and movement disability. It has also been described that these patients could not survive for a long time [9,11,16]. HLDs are a class of rare hereditary neuropathies that their related genes can be determined through latest nucleotide sequencing approaches such as NGS technologies; however, no specific therapeutic method has been developed yet [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lossof-function mutations in PYCR2 gene result in HLD10, which is identified by hypomyelination, global growth delay, microcephaly, facial dysmorphism, axial hypotonia, and movement disability. It has also been described that these patients could not survive for a long time [9,11,16]. HLDs are a class of rare hereditary neuropathies that their related genes can be determined through latest nucleotide sequencing approaches such as NGS technologies; however, no specific therapeutic method has been developed yet [17].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion in PYCR2 has been shown to cause neurodegeneration results where all cases were from a consanguineous family. Moreover, they noted that loss of PYCR2 in an in vitro design resulted in incremented susceptibility to apoptosis under oxidative stress [16].…”
Section: Discussionmentioning
confidence: 99%
“…After the first report of Nakayama et al,around 40 patients have been reported so far (Aaltio et al, 2024;Afroze & Mercimek-Andrews, 2020;Hosseini & Ghelichi-Ghojogh, 2023;Manaspon et al, 2021;Meng et al, 2017;Nakayama et al, 2015;Zaki et al, 2016). There was an adult patient from a Chinese case report, while all others were under the age of 20 (Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…The disorder is caused by alterations in the PYCR2 gene (OMIM *616406), which encodes the mitochondrial enzyme, pyrroline-5-carboxylate reductase 2, which converts pyrroline-5-carboxylate to proline. Proline is an essential amino acid for the CNS and connective tissue function 2 .…”
Section: Introductionmentioning
confidence: 99%